V. A. Zhardetsky and Siberian regionalism - A. V. Sushko; K. E. Bezrodny (Омский научный вестник: Серия "Общество. История. Современность")
In the context of events of the Russian Revolution and the Civil War in Russia the Omsk cadet Valentin Aleksandrovich Zhardetsky`s views on the Siberian regionalism are considered. He was a one of the main Kolchak regime ideologists. The source for the study is the Siberian periodicals, as well as the testimonies of our hero about the activities of the Siberian regionalists and the connection of the issue of Siberian autonomy with the international situation given to the Omsk Gubchkom on the eve of his execution. The last source is introduced into the scientific turnover for the first time. The authors conclude that the Russian nationalist V. A. Zhardetsky was one of the most consistent opponents of «Siberian selfhood» similar to the Ukrainian nationalism. His arguments about Siberian regionalism are also relevant for modern Russia, which once again faces the potential threat of separatism in Siberia